Experimental investigation on wear properties with micro-structure behavior of arecanut reinforced polymer composite material. (2021) - Joseph Irudaya Raja, S.; Sivaganesan, S.
Abstract: This study is mainly focused on wear behavior analysis of the different compositions of arecanut reinforced with polymer composite materials. The recent research is focused on the Fiber Reinforced Polymer composites (FRPC) because of the natural fiber composites are not able to meet the required mechanical properties with durability. The primary challenge of Fiber Reinforced Polymer composites is to attain high strength and less wear resistance with less weight. In this study concentrated to study the wear characteristics of reinforced polymer composite with arecanut fiber and the samples were prepared by the weight percentage with the different ratios from 0 to 30 wt%. The composite material was prepared with the help of the injection moudling technique. As per ASTM-G99 the test specimens were prepared to wear behavior analysis on the pin-on-disk wear analysis. The results were validated based on load, wear rate, sliding velocity, sliding distance, % of weight reinforcement. The wear behavior of the composite materials morphological characteristics was studied by SEM analysis and the results of SEM analysis revealed that less wear behavior is attained by applying maximum load.